2020
DOI: 10.4049/jimmunol.1901079
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Proinsulin T Cell Epitopes Restricted by Type 1 Diabetes–Associated HLA Class II Molecules

Abstract: Type 1 diabetes (T1D) is a T cell-mediated autoimmune disease in which the insulin-producing b cells within the pancreas are destroyed. Identification of target Ags and epitopes of the b cell-reactive T cells is important both for understanding T1D pathogenesis and for the rational development of Ag-specific immunotherapies for the disease. Several studies suggest that proinsulin is an early and integral target autoantigen in T1D. However, proinsulin epitopes recognized by human CD4 + T cells have not been com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Previous studies also identified antigen-specific CD4 + T cells in PB 25,[32][33][34][35] and in the islets of organ donors with T1D, including multiple islet antigens and HIPs. 11,30 This study extends that work and demonstrates that proinsulin immune reactivity is best captured by assays incorporating the PI 33-63 full-length C-peptide sequence, which contains multiple epitopes, 25,32,36 potentially increasing the pool of antigen-reactive T cells. Shorter epitopes within PI 33-63 are presented by several HLA-DR and HLA-DQ molecules, thus generating T-cell responses from individuals with varied HLA types.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies also identified antigen-specific CD4 + T cells in PB 25,[32][33][34][35] and in the islets of organ donors with T1D, including multiple islet antigens and HIPs. 11,30 This study extends that work and demonstrates that proinsulin immune reactivity is best captured by assays incorporating the PI 33-63 full-length C-peptide sequence, which contains multiple epitopes, 25,32,36 potentially increasing the pool of antigen-reactive T cells. Shorter epitopes within PI 33-63 are presented by several HLA-DR and HLA-DQ molecules, thus generating T-cell responses from individuals with varied HLA types.…”
Section: Discussionmentioning
confidence: 87%
“…This strategy is therefore particularly effective when an educated guess or inference of HLA restriction is available. An alternative methodology is the use of single HLA transfected APCs [102,[130][131][132][133]. In these experiments, the peptide is tested in antigen presentation assays utilizing panels of cell lines expressing single HLA molecules that match an allele expressed in the donor from which the T cell response is generated.…”
Section: Hla Restriction Of Epitope Responsesmentioning
confidence: 99%
“…27 Cloning, using a carboxyfluorescein succinimidyl ester (CFSE)-based cloning method, 71 and analysis of the responding CD4 + T cells revealed 17 distinct C-peptide-derived epitopes, most of which were restricted by HLA-DQ8 or HLA-DQ2. Ihantola et al 72 used a similar carboxyfluorescein succinimidyl ester-based cloning approach to analyze CD4 + T-cell responses in individuals who did not have T1D but carried T1Dassociated HLA alleles. Because responses to PI peptides could not be detected in these individuals without T1D, they added interleukin (IL)-2 and IL-7 to augment antigen-specific proliferation.…”
Section: Cd4 + T-cell Responses To Proinsulin Detected In Peripheral Bloodmentioning
confidence: 99%